Isolation and Cultivation of Porcine Endothelial Cells, Pericytes and Astrocytes to Develop an In Vitro Blood-Brain Barrier Model for Drug Permeation Testing - Verena Ledwig; Stephan Reichl (MDPI AG, 2023)
The blood-brain barrier (BBB) is the bottleneck in the development of new drugs to reach the brain. Due to the BBB, toxic substances cannot enter the brain, but promising drug candidates also pass the BBB poorly. Suitable in vitro BBB models are therefore of particular importance during the preclinical development process, as they can not only reduce animal testing but also enable new drugs to be developed more quickly. The aim of this study was to isolate cerebral endothelial cells, pericytes, and astrocytes from the porcine brain to produce a primary model of the BBB. Additionally, as primary cells are well suited by their properties but the isolation is complex and better reproducibility with immortalized cells must be ensured, there is a high demand for immortalized cells with suitable properties for use as a BBB model. Thus, isolated primary cells can also serve as the basis for a suitable immortalization technique to generate new cell lines. In this work, cerebral endothelial cells, pericytes, and astrocytes were successfully isolated and expanded using a mechanical/enzymatic method. Furthermore, in a triple coculture model, the cells showed a significant increase in barrier integrity compared with endothelial cell monoculture, as determined by transendothelial electrical resistance measurement and permeation studies using sodium fluorescein. The results demonstrate the opportunity to obtain all three cell types significantly involved in BBB formation from one species, thus providing a suitable tool for testing the permeation properties of new drug candidates. In addition, the protocols are a promising starting point to generate new cell lines of BBB-forming cells as a novel approach for BBB in vitro models.